2009
DOI: 10.1073/pnas.0911937106
|View full text |Cite
|
Sign up to set email alerts
|

Coupling ATP utilization to protein remodeling by ClpB, a hexameric AAA+ protein

Abstract: ClpB and Hsp104 are members of the AAA؉ (ATPases associated with various cellular activities) family of proteins and are molecular machines involved in thermotolerance. They are hexameric proteins containing 12 ATP binding sites with two sites per protomer. ClpB and Hsp104 possess some innate protein remodeling activities; however, they require the collaboration of the DnaK/Hsp70 chaperone system to disaggregate and reactivate insoluble aggregated proteins. We investigated the mechanism by which ClpB couples A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
65
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 39 publications
(48 reference statements)
6
65
0
Order By: Relevance
“…S1) [16]. We also compare data presented herein with recently published results obtained with mixing experiments, in which different amounts of homohexamers of wt ClpB and some of the protein mutants used in this study are mixed before the experiment [16,18].…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…S1) [16]. We also compare data presented herein with recently published results obtained with mixing experiments, in which different amounts of homohexamers of wt ClpB and some of the protein mutants used in this study are mixed before the experiment [16,18].…”
Section: Resultssupporting
confidence: 66%
“…A recent study with TClpB has used this property to show that insertion of an inactive subunit within the hexamer impairs its chaperone activity [16]. Using the same mixing approach, it has been recently shown that ClpB can modify the mechanism of ATP utilization depending on the substrate and the presence of the DnaK system [18]. While in the absence of DnaK the protein can remodel the substrate with approximately three active protomers per hexamer, in the presence of DnaK the characteristics of the active hexamer have not been defined so accurately.…”
Section: Introductionmentioning
confidence: 99%
“…As anticipated, many of our substrates were not reactivated, including chemically denatured FFL, which requires both Hsp70 and Hsp40 for protein refolding (42,43). Strikingly, we found that both aggregated β-gal and EGFP, which do not require Hsp70/40 for reactivation (6,31,44), could be rescued by Hsp104 together with full-length Hsp70 (Fig. 5A and Fig.…”
Section: Resultsmentioning
confidence: 54%
“…We propose that this signaling network is crucial to sense the nucleotide state in the adjacent subunit and to reset the nucleotide cycle in the ClpB ring following ATP hydrolysis. The existence of an ISS network that regulates ATP hydrolysis in diverse AAA+ ring complexes is also consistent with a sequential ATP-hydrolysis mechanism proposed for ClpB (45,46) and Hsp104 (47), with four out of six subunits in the ClpB homohexamer occupied by nucleotides at any one time (46). This model is similar to the staircase mechanism proposed for the T7 gene 4 ring helicase (48), and is consistent with the nucleotide occupancy observed in the crystal structure of an engineered, covalently linked ClpX hexamer (11).…”
Section: Discussionmentioning
confidence: 51%